Intertekstual Lakon Randai Sabai Nan Aluih Karya Efyuhardi Dalam Lakon Pray - Monita Precillia (TAMUMATRA, 2023)
The article entitled Intertextual of the play Randai Nan Aluih by Efyuhardi in the play Pray For Sabai by Edy Suisno is a qualitative research in the form of descriptive analysis. The Pray For Sabai text is the result of the Intertextual Manuscript of Sabai Nan Aluih which is in accordance with the kaba that is developing in society. This paper aims to describe the background and process of the emergence of the text Pray For Sabai by Edy Suisno. We can say that it is intertextual that it rejects the establishment of a text, where Pray For Sabai uncovers the possibilities that exist in Sabai Nan Aluih. Intertextual in Pray For Sabai not only changes the storyline but also changes the identity and character of the characters. The character of Sabai Nan Aluih was originally the biological child of Sadun Saribai and Rajo Babanding, but it turned out that he was only an adopted child. Sabai Nan Aluih is the biological child of Rajo Nan Panjang and a beautiful maid who he raped.